Experimental Study for Influence of Surfactants Chemical Microstructures on Wetting Effect about Coal Dust in Tongchuan Mining Area - Youying Ma; Yuying Wang; Qingtao Zhang (Journal of Chemistry)
Because of the unsatisfactory dust suppression efficiency, coal dust still threatens production safety and personnel health. In order to understand the influence of the chemical microstructures of the surfactant on the wetting ability and to facilitate the rapid selecting of surfactants with good wetting performances for specific coal dust, fatty acid methyl ester ethoxylate (FMEE), dodecyl dimethyl betaine (BS-12), sodium fatty acid polyoxyethylene ether carboxylate (AEC), and dodecyl dimethyl benzyl ammonium chloride (DDBAC) were selected in this paper to study the wetting ability of these four surfactants on the bituminous coal dust in Tongchuan, Shaanxi province of China. First, the main functional groups and carbon composition of the coal dust and surfactants were determined by Fourier transform infrared spectroscopy and carbon-13 nuclear magnetic resonance spectroscopy experiments. Second, the drop shape analysis system DSA100 was used to measure the equilibrium contact angle of the surfactant solution with a concentration of 0.06% on bituminous coal dust. The relationship between the chemical microstructures of surfactants and contact angles was analyzed, and the main influencing factors were obtained. The results showed that the contact angle of DDBAC on coal sample dust was the smallest. In addition, the contents of hydroxyl, aromatic ring carbon, unprotonated carbon, and bridged aromatic carbon in surfactants had significant linear correlations with wettability, and the increase of their contents would lead to the decrease of contact angle. According to the results of correlation analysis and curve fitting, the evaluation model of influencing factors on the wettability to bituminous coal dust was established.